Anxiety, Depression, and Sleep Quality of Nursing Clinical Practitioner Students During the COVID-19 Pandemic - Esti Widiani; Rahmawati, Ira; Hidayah, Nurul (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
The nursing clinical practice program is an orientation for students to apply theory to practice and gain competence in nursing skills before graduation. The COVID-19 pandemic brings a new reality to nursing students who carry out clinical practice to be more professional. This condition triggers increased cases of anxiety and depression in nursing students. This study aims to determine the anxiety, depression, and sleep quality of nursing students undergoing clinical practice during the COVID-19 pandemic. The population in this study was 1320 nursing students. This study used a cross-sectional approach to 377 nursing students. Research respondents were taken using a purposive sampling technique. A generalized Anxiety Disorder 7‐item scale (GAD-7) was used to collect anxiety data. Depression was measured using the Patient Health Questionnaire (PHQ-9). Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Based on the Spearman rank correlation test results, there is a correlation between sleep quality scores and depression scores with p = 0.000 (p < 0.01) and r = 0.528. There is a correlation between anxiety scores and sleep quality scores with p = 0.000 (p < 0.01) and r = 0.448. There is a correlation between anxiety scores and depression scores with p = 0.000 (p < 0.01) and r = 0.829. The quality of student sleep needs to be maintained to help reduce anxiety and depression in students practicing clinically. The role of professional clinical instructors in assisting students is needed to assist students in carrying out clinical practice well.